Eutrophication triggers contrasting multilevel feedbacks on litter accumulation and decomposition in fens. Issue 10 (1st September 2016) - Emsens, W.‐J.; Aggenbach, C. J. S.; Grootjans, A. P.; Nfor, E. E.; Schoelynck, J.; Struyf, E.; van Diggelen, R.
Abstract: Eutrophication is a major threat for the persistence of nutrient‐poor fens, as multilevel feedbacks on decomposition rates could trigger carbon loss and increase nutrient cycling. Here, we experimentally investigate the effects of macronutrient (NPK) enrichment on litter quality of six species of sedge ( Carex sp.), which we relate to litter decomposition rates in a nutrient‐poor and nutrient‐rich environment. Our research focused on four levels: we examined how eutrophication alters (1) fresh litter production ("productivity shift"), (2) litter stoichiometry within the same species ("intraspecific shift"), (3) overall litter stoichiometry of the vegetation under the prediction that low‐competitive species are outcompeted by fast‐growing competitors ("interspecific shift"), and (4) litter decomposition rates due to an altered external environment (e.g., shifts in microbial activity; "exogenous shift"). Eutrophication triggered a strong increase in fresh litter production. Moreover, individuals of the same species produced litter with lower C:N and C:P ratios, higher K contents, and lower lignin, Ca and Mg contents (intraspecific shift), which increased litter decomposability. In addition, species typical for eutrophic conditions produced more easily degradable litter than did species typical for nutrient‐poor conditions (interspecific shift). However, the effects of nutrient loading of the external environment (exogenous shift) were contradictory. Here, interactions between litter type and ambient nutrient level indicate that the (exogenous) effects of eutrophication on litter decomposition rates are strongly dependent of litter quality. Moreover, parameters of litter quality only correlated with decomposition rates for litter incubated in nutrient‐poor environments, but not in eutrophic environments. This suggests that rates of litter decomposition can be uncoupled from litter stoichiometry under eutrophic conditions. In conclusion, our results show that eutrophication affects litter accumulation and ‐decomposition at multiple levels, in which stimulatory and inhibitory effects interact. The cumulative effect of these interactions ultimately determine whether peatlands remain sinks or become sources of carbon under eutrophic conditions.